Implementation of the policy of equalizing supervisory positions into functional positions at borneo University Tarakan - Mirayanthi, Dewi (Jurnal Mantik, 2024)
This study aims to evaluate the implementation of the Minister of Administrative Reform and Bureaucratic Reform Regulation Number 28 of 2019 concerning Equalization of Administrative Positions into Functional Positions at the University of Borneo Tarakan (UBT). The research method used is qualitative, with data collection through interviews, observation, and documentation. The results showed that policy implementation at UBT was not optimal. There are major obstacles in terms of communication, where information regarding equalization of positions is conveyed through private networks without adequate socialization. In addition, there are resource constraints, such as the incompatibility of the educational background of civil servants with the functional positions held and the limitations of supporting facilities. The bureaucratic structure that has not adjusted the Organization and Work Procedures (OTK) and Standard Operational Procedure (SOP) is also an obstacle. In addition, there are obstacles outside the indicator, namely the collection of credit numbers. In conclusion, to overcome these obstacles, it is recommended that UBT hold a more comprehensive socialization, conduct a more detailed position mapping, improve supporting facilities, and immediately propose changes to the OTK and SOP to the Ministry of Education, Culture, Research and Technology. The implementation of this position equalization requires more supportive regulations and credit score assessment submitted to UBT